Pengembangan Desain Pembelajaran PAI Di Pondok Pesantren Kreatif Agro Nuur El-Falah Salatiga - Tri Hartono; Dhenis Agus Saputro (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
Islamic boarding school is a place for students to live and study, especially religious knowledge. The development of Islamic boarding schools should start from the learning system, learning methods or learning media to support the achievement of learning objectives of Islamic religious education. Besides boarding schools also need to develop existing local potential through entrepreneurship or skills for students as provisions after returning to the community. Like Agro Nuur Islamic Boarding School El-Falah Salatiga, which always tries to innovate in institutions or learning. In this Islamic Boarding School Institution is always renewing the organizational structure per year, as well as making an academic calendar Islamic Boarding School. In the Islamic Religious Education learning design Agro Islamic Boarding School Nuur El-Falah has at least two unique things compared to Islamic boarding schools in general, namely this cottage implements Learning Design Takror and Study Design of the Book of the Koran Extra. This learning design is a form of boarding school innovation to increase the spirit of students in learning. In terms of instructional media, Agro Nuur El-Falah Islamic Boarding School combines classical learning systems with modern systems, so that in practice they continue to use traditional methods such as sorogan and bandongan but are also often supported by modern equipment such as computers and LCDs. Besides this the cottage also develops the local potential of agriculture as a provision for the students to deal with future life in the community.